2012
DOI: 10.1038/nature11775
|View full text |Cite
|
Sign up to set email alerts
|

LTP requires a reserve pool of glutamate receptors independent of subunit type

Abstract: SummaryLong-term potentiation (LTP) of synaptic transmission is thought to be a key cellular mechanism underlying memory formation. A widely accepted model posits that LTP requires the cytoplasmic tail of the AMPA receptor subunit GluA1. To find the minimum necessary requirement of the GluA1 C-tail for LTP in CA1 hippocampal pyramidal neurons, we used a single-cell molecular replacement strategy to replace all endogenous AMPA receptors with transfected subunits. In striking contrast to the prevailing model, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
311
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(346 citation statements)
references
References 42 publications
32
311
2
1
Order By: Relevance
“…The concept that subunit composition is the defining factor in the AMPAR trafficking underlying plasticity has been called into question by acute AMPAR subunit knockdown and molecular replacement studies 18,19 . Contrary to expectation, using a strong LTP induction protocol it was reported that no specific AMPAR subunit is required for LTP.…”
Section: Subunit Independent Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept that subunit composition is the defining factor in the AMPAR trafficking underlying plasticity has been called into question by acute AMPAR subunit knockdown and molecular replacement studies 18,19 . Contrary to expectation, using a strong LTP induction protocol it was reported that no specific AMPAR subunit is required for LTP.…”
Section: Subunit Independent Traffickingmentioning
confidence: 99%
“…However, as discussed below, this model has been challenged by several recent reports. These include reports interrogating the roles in activity-dependent trafficking and synaptic plasticity of specific AMPAR subunits 18,19 , their C-terminal tails and PDZ ligands 20,21 and changes to their phosphorylation status 22 . Taken together these findings have initiated a reappraisal of the core mechanisms underlying synaptic incorporation of AMPARs.…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
“…, 2 0 0 7 ) . A l s o s e v e r a l m e c h a n i s m s t o counterbalance impaired Hebbian plasticity exist (Granger et al, 2013). From this perspective, it is not surprising that, in the absence of GluA4, no dramatic defects in overall circuit development were detected; no differences in either mEPSC frequency or amplitude were observed in CA1 pyramidal neurons between WT and GluA4-/-mice.…”
Section: Physiological Significance Of Glua4-dependent Plasticity In mentioning
confidence: 99%
“…GluA1 and GluA4 containing AMPAR trafficking is mediated by interaction of GluA1-MPR and GluA4-MPR with intracellular proteins, such as protein 4.1N and PKCγ (Shen et al, 2000;Coleman et al, 2003;Correia et al, 2003;Chen et al, 2005;Gomes et al, 2007;Lin et al, 2009). However, of note a recent study has shown that the MPR of GluA1 is not needed for protein trafficking or LTP in hippocampal CA1 (Granger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%